KARAKTERISTIK FISIKOKIMIA DAN SENSORI KUE BANGKIT BERBAHAN PATI SAGU, TEPUNG TEMPE DAN TEPUNG UBI JALAR UNGU - SELVI MUSTIKA SARI; RASWEN EFENDI; NETTI HERAWATI (Jurnal Sagu, 2016)
The purpose of this study was to determine the effect of using sago starch, tempe flour and purple sweet potatoflour to the characteristics physicochemical and sensory of the cookies and meet the quality standard ofcookies (SNI 01-2973-1992). The research used a Completely Randomized Design (CRD) with five treatmentand four replications. The treatment in this study were K1 (sago starch 100%), K2 (sago starch 60%, tempehflour 20%, purple sweet potato flour 20%), K3 (sago starch 50%, tempeh flour 25%, purple sweet potato flour25%), K4 (sago starch 40%, tempeh flour 30%, purple sweet potato flour 30%), K5 (sago starch 30%, tempehflour 35%, purple sweet potato flour 35%). The data obtained were statistically analyzed using analysis ofvariance (Anova). If F count is greater than or equal to F table, then conduted a further test with Duncan’sNew Multiple Range Test (DNMRT) at the level of 5%. The results showed that the treatment significantlyeffect to the moisture content, ash content, protein content, analysis texture, descriptive sensory assessmentand hedonic sensory assessment and non significant on the overall hedonic ratings. The best cookies in thisresearch is was K3 with has 2.95% of moisture content, 1.14% of ash content, 8.86% of protein content 4.30kgf of texture, coloured purple, sweet scent purple sweet potato, slightly brittle texture and having sweetness.